Income taxation and the timing of marriage - Alexander Fink (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
By modifying the incentive structure, taxes affect human behavior. I investigate how the German income tax code influences the timing of civil marriages. The German income tax code contains provisions from which married couples stand to benefit relative to unmarried couples. If their individual incomes differ, legally married couples may benefit from filing their income taxes jointly due to a progressive income tax. The gain from joint taxation for married couples accrues in every year. Couples also enjoy it in the year in which they marry, independent of the month of the marriage. I use data from the German Socio-Economic Panel to the hypothesis that couples with larger gains from joint taxation are more likely to marry late in the current year instead of early in the subsequent year. The results provide strong support for the hypothesis that pecuniary gains from joint taxation incentivize couples to prepone their marriages to the current year.
Keywords: J12; D10; H24; 330